Christianity and black masculinity in James Baldwin’s Blues for Mister Charlie and August Wilson’s Joe Turner’s come and gone / Cristianismo e masculinidade em Blues for Mister Charlie, de James Baldwin e Joe Turner’s come and gone, de August Wilson - Laranjeira, Delzi Alves (Numen, 2014)
Abstract Religion works as a modeling system, that is, it rules and orients a notion of reality and how to act according to its truths and assumptions. In William Baldwin’s Blues for Mister Charlie and August Wilson’s Joe Turner’s come and gone, the main characters undergo a deep identity crisis, emphasized by the confrontation of Christian premises strongly taken for granted with new ways of conceiving and realizing spirituality. By analyzing the way this crisis is established and solved within the plays it is possible to identify a criticism to the notion of black masculinity embedded in a Christian perspective. Keywords: Christianity; Black masculinity, Identity Resumo A religião opera como um sistema modelador, ou seja, define e orienta uma noção de realidade e de como agir de acordo com suas concepções. Nas peças Blues for Mister Charlie, de William Baldwin e Joe Turner’s come and gone, ambos dramaturgos afro-americanos, seus protagonistas enfrentam uma aguda crise de identidade, acentuada pelo confronto entre premissas cristãs profundamente introjetadas e novas formas de conceber e vivenciar a espiritualidade. A análise de como essa crise se estabelece e é resolvida nas peças permite identificar críticas a uma noção de masculinidade fortemente atrelada a uma perspectiva cristã. Palavras-chave: Cristianismo, masculinidade negra, identidade.